Coesite in suevite from the Ries impact structure (Germany): From formation to postshock evolution. (10th March 2017) - Fazio, Agnese; Mansfeld, Ulrich; Langenhorst, Falko
Abstract: Coesite is one of the most common and abundant high‐pressure phases occurring in impactites. The mechanism of formation of coesite and its postshock evolution is revisited in this paper based on Raman microspectroscopy, and scanning and transmission electron microscopy of a coesite‐bearing suevite from the Ries impact structure. Our data indicate that coesite forms through a single process, i.e., by crystallization from high‐pressure silica melt, and that its formation is related to fluid inclusions in precursor quartz. During the postshock phase, coesite aggregates are partially modified by annealing and interactions with fluids. In an early stage of the postshock evolution, coesite is back‐transformed to quartz and the surrounding diaplectic glass devitrifies into β‐cristobalite, which transforms into α‐cristobalite and then into microcrystalline quartz during subsequent stages of the postshock evolution. Altogether these postshock modifications result in a significant volume loss and extensional fracturing. During a late postshock stage, the fractures are filled with clay minerals due to circulation of hydrothermal fluids.